Investigating the association between underlying factors, eating habits, and obesity in girls aged 9-11: a case control study - Kheiltash, Azita; Khajehnasiri, Farahnaz; Khatami, Farnaz; Nikbakht, Marzie; Dorosti, Ahmad Reza (Progress in Nutrition, 2018)
Aims: Over the past few years, the prevalence of childhood obesity has been increasing. This study aimed to assess the factors leading to obesity in female children in Iran. Methods: This is a case-control study of 9-11 year old school girls conducted in 2013 using stratified random sampling. The participants had not experienced menstruation and had not received any multivitamin or supplements at the time of the study. Seventy five students, with a Body Mass Index (BMI) ≥95th percentile, were considered as obese while another group of 75 students, with BMI percentiles 15≤BMI≤85, were selected as control group. The data on underlying factors were collected through interviews while the data associated with eating habits, including dietary intake, were gathered using 24-hour dietary recall questionnaire. Results: Daily caloric intakes observed in the obese and normal children were 1881±755 and 1609±529 kcal, respectively (p=0.01). Daily caloric intake was significantly correlated to weight (p=0.03) and BMI (p=0.01). History of obesity among first-degree relatives (p<0.001) and TV watching habits (p<0.001) showed significantly higher levels in obese children than the levels found in the control group. Using t-Test analysis, a statistically significant association was found between BMI in the obese adolescents and intake of vitamin B1 (p=0.02), B2 (p=0.011), and B6 (p=0.05). Conclusions: Our findings suggest that food intake pattern and sedentary behaviours in obese girls are major risk factors leading to metabolic disorders in the future.